Pengaruh Kualitas Pelayanan, Pengetahuan, dan Kepercayaan terhadap Keputusan Muzakki dalam Membayar Zakat di Lembaga Amil Zakat Nurul Fikri Zakat Center Area Sampit - Aisyah, Siti; Sutejo, Bambang (Keizai, 2020)
This study aims to examine the effect of the influence of service quality, knowledge, and trust on Muzakki's decision to pay zakat at the Amil Zakat Institution Nurul Fikri Zakat Center Sampit Area. Data was collected through questionnaires with 100 respondents from muzak who paid zakat at Nurul Fikri Zakat Center Sampit Area. The sampling method and technique used are the Non-Probability Sampling Method and uses accidental sampling technique. T-test to test and prove the research hypothesis. The results of the t-test analysis showed that the service quality variable did not significantly influence Muzakki's decision to pay zakat at the Amil Zakat Institution Nurul Fikri Zakat Center Sampit Area, as evidenced by a regression value of 0.131 and a calculated value of 0.545 with a significance level of 0.587. The knowledge variable does not significantly influence the decision to pay Zakat at the Amil Zakat Institution Nurul Fikri Zakat Center Sampit Area, which proves with a regression value of 0.015 and a calculated value of 0.192 with a significant level of 0.848. The Trust variable has a significant positive effect on the decision to pay Zakat at the Amil Zakat Institution Nurul Fikri Zakat Center Sampit Area, which proves with a regression value of 0.273 and a calculated value of 3.422 with a significant level of 0.001.